The Interlanguage Analysis Of The Senior High School Students Of Sman I Dagangan Madiun - Royani, Sulis Ida, Prof. Dr. Endang Fauziati, M.Hum, Dr. Anam Sutopo, M.Hum (2015)
As language communication, both written or orally, English is very important to study because of it is universal language. However, it is not easy to study, particularly to students in senior high school. On the other hand, English is also difficult for Indonesian students to use the structure of sentences correctly. This is mostly because the students are influenced by their mother tongue on the acquisition of the new structure. However, the students are still weak in English, especially in their writing skill; they still seem to commit errors in all aspect of language. Based on the errors made by students, the writer intends to study about The Interlanguage Analysis of The Senior High School Students of SMAN I Dagangan Madiun. This study is concentrated on systems of inter language. The type of this study is qualitative research which aims at explains of inter language system types which based on the collected data from students writing test. The subjects of this research are 30 students, 20 are females and 10 males in X class. The method of collecting the data are observation and documentation. The result of this research shows that the three kinds of interlanguage systems, they are interlanguage systems used by students of SMAN I Dagangan Madiun to express present event, to express past event and to express future event. The first kind is nine types of interlanguage system. The second kind is six types of interlanguage systems and the third is four types of interlanguage systems. Based on the result of this study, the writer concludes that all of interlanguage systems used by the students are in general, it means as the learners for second language are some factors influenced them. Especially the students are influenced by mother tongue on the acquisition of the new structure. In the meantime, the most important of this case is how the teachers correct the errors in every writing test. The students errors in writing test need to do the remedial in every test.